RESEARCH ON THE READINESS AND MOTIVATION OF NURSING STUDENTS TO PARTICIPATE IN INTERNATIONAL VOLUNTEER INITIATIVES - Snezhanka Dragusheva; Mariya Stamova-Georgieva; Lilia Georgieva; Nedyalka Boycheva (Journal of IMAB - Annual Proceeding (Scientific Papers), 2026)
Over the last century, the nursing profession has undergone a dramatic development – from a volunteer, through a doctor's assistant, to a nurse with an independent role. Their participation in voluntary initiatives is essential for addressing challenges faced by many countries. The purpose of this study is to analyze the motivation and willingness of nursing students to participate in volunteer initiatives abroad. Material and methods: The study included 194 (96.5%) women and 7 (3.5%) men. The structural distribution of the 201 participants in the study from different Universities teaching "Nursing care". The results were processed with the statistical package SPSS. 21. A significant difference was considered p